1972
DOI: 10.1161/01.res.30.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Hypertension on the Rat Aortic Wall and Their Relation to Concurrent Aging Changes: MORPHOLOGICAL AND CHEMICAL STUDIES

Abstract: The effects of long-term (16 months) hypertension on the thoracic aorta of male rats were compared to previously reported short-term (2.5 months) changes and to concurrent aging changes. Hypertension was produced by clipping a renal artery. Although short-term hypertension was characterized by a disproportionate increase in noncollagenous alkali-soluble proteins, which have been attributed primarily to vascular smooth muscle, with long-term hypertension there was no further increase in these proteins but inste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
165
3
4

Year Published

1980
1980
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(183 citation statements)
references
References 23 publications
11
165
3
4
Order By: Relevance
“…Certain conditions, such as hypertension, atherosclerosis, and intimal injury, stimulate VSMCs to produce extra collagen in the vessel wall. 30,31 Our study supports this view by showing a 38% increase in total collagen content per centimeter of aortic segment in SHRs over WKY rats. Previous studies revealed that arterial collagen content increased progressively with aging and became more insoluble and crosslinked.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Certain conditions, such as hypertension, atherosclerosis, and intimal injury, stimulate VSMCs to produce extra collagen in the vessel wall. 30,31 Our study supports this view by showing a 38% increase in total collagen content per centimeter of aortic segment in SHRs over WKY rats. Previous studies revealed that arterial collagen content increased progressively with aging and became more insoluble and crosslinked.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies revealed that arterial collagen content increased progressively with aging and became more insoluble and crosslinked. 30,32 In sharp contrast, vascular elastin synthesis is active in newborn and young rats, and becomes quiescent in aged animals resulting a reduced elastin:collagen ratio. 33 Elastin is more extensible, but collagen fibers are very rigid.…”
Section: Discussionmentioning
confidence: 99%
“…"3 In these conditions, 0.5 gsec represents 0. 4 E 8MHZ E 0a-2se---sc, t The time delay of the first velocity wave (t,) and the time delay of the last one (t2) indicate the region where the sample volume is close to the proximal and the distal arterial walls from the transducer ( fig. 2).…”
Section: Materials and Methods Patientsmentioning
confidence: 99%
“…LARGE ARTERIES of hypertensives have been shown to be thicker and stiffer than normal vessels in both experimental animals' 4 and in human subjects.5 ,' However, in humans, these observations resulted either from invasive studies of the pressurevolume relationship of the brachial artery in vivo,5 or from the measurements of the thickness of the aorta at autopsy.6 Little information is available for intact large arteries, probably because of lack of appropriate techniques.…”
mentioning
confidence: 99%
“…The aorta experimental evidence Wolinsky (1972) and Karsner (1938) have pointed out the similarity between the changes in the aorta in hypertension and in ageing. These include thickening of the wall, dilatation of the lumen, increase in muscle collagen, elastin, mucopolysaccharides and oxygen consumption and decreased distensibility and elasticity.…”
Section: Arteriosclerosismentioning
confidence: 90%